Pre-Symptom Detector of Root Disease Palm Oil (Ganoderma) Trunk Based on LoRa and IoT - Hadary, Ferry; Saziati, Ochih; Muhaimin, Ahmad Dzakiyuddin (Universitas Syiah Kuala, 2024)
The stem rot disease caused by the Ganoderma boninense is a type of disease that is deadly to oil palm plants and can cause a significant reduction in oil palm productivity. Difficulty in detecting disease infected oil palm plants is cause of the high risk of plan death due to the condition and risk of oil palm plants being affected by disease as early as possible. The system used is Long Range (LoRa) technology which utilizes radio frequencies as signal transmission between transmitter and receiver devices. The transmitter device is equipped with TGS 2611, MQ-138, MS1100 and TGS822 sensors as a tool for detecting ganoderma disease and is also equipped with a GPS sensor which functions to map trees affected by the disease. Meanwhile, the receiver as the recipient of the data that has been sent by the transmitter via LoRa will be forwarded to BIynk Apps via the internet network, thus forming an IoT (Internet of Things) system. This technology helps monitor oil palm plantations more efficiently because it can be monitored in real time on a smartphone application. The research results show that the four sensors can detect levels of volatile organic compounds (VOC) from ganoderma fungi with three classification; healthy, moderate and sick.